Ways of Using Games in Forming the Activity of Preschool Children (Eurasian Journal of Learning and Academic Teaching, 2023)
The leading activity of preschool children is the game. The game activity of preschool children has attracted the attention of many scientists for centuries. Children of preschool age strive to reflect all aspects of our busy life in their play activities.